2020
DOI: 10.1080/22221751.2020.1852893
|View full text |Cite
|
Sign up to set email alerts
|

A lateral flow immunoassay test performance in SARS-CoV-2 seroprevalence surveys: a validation study among healthcare workers

Abstract: The objective of this study was to evaluate the validity and reliability of NG-Test® when used as a finger-prick test on healthcare workers and to compare it to the ELISA Wantai Immunoassay. Fifty-one healthcare workers who were RT-PCR SARS-CoV-2 positive and 59 who were RT-PCR SARS-CoV-2 negative accepted to participate in this study. They were subjected to an NG-Test® finger-prick test and collection of a blood sample on the same day. A second NG-Test® on another finger was performed for the first 30 cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…IgM test lines accounted for more than two-thirds (67.9%) of cross-reacting test lines. False-positive IgM test lines in COVID-19 Ab RDTs have been reported before [ 18 , 42 , 51 ], and given the comparable kinetics of IgM and IgG, selective testing for IgM has been questioned [ 52 ]. In that regard, a seroprevalence study in Spain took into account only the IgG results of the COVID-19 Ab RDT used, while disregarding the IgM results [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgM test lines accounted for more than two-thirds (67.9%) of cross-reacting test lines. False-positive IgM test lines in COVID-19 Ab RDTs have been reported before [ 18 , 42 , 51 ], and given the comparable kinetics of IgM and IgG, selective testing for IgM has been questioned [ 52 ]. In that regard, a seroprevalence study in Spain took into account only the IgG results of the COVID-19 Ab RDT used, while disregarding the IgM results [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our validation study 12 demonstrated that SARS-CoV-2 serological test with LFIAT had a predictive positive value of 49.7% and a negative predictive value of 99.7% in our population study for IgG. We thus determined the SARS-CoV-2 serological status (negative / positive) using two distinct approaches.…”
Section: Discussionmentioning
confidence: 93%
“…Our study also has several strengths. The determination of SARS-CoV-2 status was based on a LFIA test that we previously validated 12 . Our knowledge of the quality of both the negative and positive predictive values allowed us to include these data in our models, using multiple imputation after stratification on the LFIA test response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG with a sensitivity of 82.5% and a specificity of 98%. 13 If the LFIAT was positive, a venous blood sample (7 mL) was proposed to confirm the serological status (Wantai SARS-CoV-2 Ab ELISA, Beijing, China).…”
Section: Serological Statusmentioning
confidence: 99%